Engineering Large Anisotropic Magnetoresistance in La0.7Sr0.3MnO3 Films at Room Temperature. (4th May 2017) - Perna, Paolo; Maccariello, Davide; Ajejas, Fernando; Guerrero, Ruben; Méchin, Laurence; Flament, Stephane; Santamaria, Jacobo; Miranda, Rodolfo; Camarero, Julio
Abstract : The magnetoresistance (MR) effect is widely used in technologies that pervade the world, from magnetic reading heads to sensors. Diverse contributions to MR, such as anisotropic, giant, tunnel, colossal, and spin‐Hall, are revealed in materials depending on the specific system and measuring configuration. Half‐metallic manganites hold promise for spintronic applications but the complexity of competing interactions has not permitted the understanding and control of their magnetotransport properties to enable the realization of their technological potential. This study reports on the ability to induce a dominant switchable magnetoresistance in La0.7 Sr0.3 MnO3 epitaxial films at room temperature (RT). By engineering an extrinsic magnetic anisotropy, a large enhancement of anisotropic magnetoresistance (AMR) is achieved which at RT leads to signal changes much larger than the other contributions such as the colossal magnetoresistance. The dominant extrinsic AMR exhibits large variation in the resistance in low field region, showing high sensitivity to applied low magnetic fields. These findings have a strong impact on the real applications of manganite‐based devices for the high‐resolution low field magnetic sensors or spintronics. Abstract : A dominant switchable magnetoresistance, at room temperature, in half‐metallic La0.7 Sr0.3 MnO3 epitaxial films is achieved by engineering an extrinsic magnetic anisotropy, through the use of substrates with progressively larger miscut angles. This leads to an enhancement of the anisotropic magnetoresistance (AMR) signal, much larger than the other contributions such as the colossal magnetoresistance (CMR), enabling the realization of the manganite technological potential.